Performance of IC Engines Using Chicken Waste as Biofuel, CNT and MnO Nano-Biofuels and Diesel Fuel: A Comparation Study - Sathish Thanikodi; Sanjay Mavinkere Rangappa; Abdi Hanra Sebayang; Suchart Siengchin (Universitas Muhammadiyah Magelang, 2023)
Biofuel production and its properties improvisation are the wide areas of research in internal combustion (IC) engines. This research derived biofuel from industrial chicken waste. Nanofuels were produced in this study by adding 40 nm-sized nanoparticles of carbon nanotube (CNT) and manganese oxide (MnO) with a variation of 100 to 200 ppm to the derived oil. Four fuel blends (biofuel (B), B with CNT, B with MnO, and B with CNT+MnO) were compared to the performance of diesel fuel in a 3.5 kW CI engine. The combustion process (peak pressure and heat release), brake thermal efficiency (BTE), and exhaust emissions (CO, HC, NOx, and CO2) were used as parameters to evaluate the fuel’s performance. The result revealed that nanofuel outperformed both diesel fuel and biofuel. The addition of 200 ppm CNT in biofuel enhanced the fuel properties, resulting in higher BTE by 28% and 9.7% compared to diesel fuel and biofuel. The CNT-biofuel also generated fewer emissions compared to diesel fuel by 26%, 9.4%, and 25% for NOx, HC, and CO gases respectively.